Measurement of the fresh rheological properties of material in 3D printing - Liu, Zhixin (2018)
3D printing of cementitious material/concrete is getting more and more attention from both industry and academic in recent years. Unlike traditional construction, fresh cementitious material pumpability and buildability is crucial in 3D printing process. Only with appropriate pumpability and buildability, cementitious material can be transported in the delivery system smoothly then be deposited layer by layer firmly. The pumpability and buildability have closely relationship with fresh rheological properties of the cementitious material. In this paper, the fresh rheological properties of three kinds of materials were measure via the large gap viscometer. Two different models (Bingham model, modified Bingham model) were applied to derive the yield stress and plastic viscosity of each cementitious material. Experimental results show that the predicted yield stress and plastic viscosity varies a lot even for the same material and the deviation of plastic viscosity is much larger than that of the yield stress.